The City as Nation: Nick Joaquin's Manila, My Manila as Nationalist History - van der Wall, Hidde (Archīum Ateneo, 2019)
This article discusses Nick Joaquin’s Manila, My Manila (1989/1999) as an example of how his historiographical work tends to be more conventional in terms of the nationalism that dominates Philippine historiography, and has a more complex relationship to this discourse than existing analyses tend to suggest. While his veneration of the Spanish colonial period is indeed unconventional, his book leaves the main problem of nationalist discourse untouched as it maintains the essentialist notion of an identifiable national community projected backwards into time. The book fails to capitalize on the potential for disrupting national paradigms that city narratives offer. Rather than breaking up narratives of nationalism, it creates a new one, homogenizing Philippine history around a linear history of the city. It imagines Manila as the continuously endangered seed of the nation, which miraculously overcomes the multitude of threats thrown its way. While the narrative glosses over the inherent diversity of the nation, it also exposes an essentialist, teleological, and metaphysical historical vision. The ambiguity of Joaquin’s vision, and of his relationship with the tradition of Philippine historiography, then, lies in his outward rejection of the essentialism inherent to nationalist notions on the one hand, and the determinism governing his homogenizing narratives on the other.